2022
DOI: 10.1186/s12910-021-00737-w
|View full text |Cite
|
Sign up to set email alerts
|

The role of community advisory boards in community-based HIV clinical trials: a qualitative study from Tanzania

Abstract: Background Community Advisory Boards (CAB) have become essential organs of involving communities in HIV clinical trials especially in developing countries. However, limited empirical evidence exists on the role of CABs in low and middle-income countries including Tanzania. This study aims at exploring the role of CABs in community-based HIV clinical trials conducted in Tanzania. Methodology We adopted a phenomenological approach to purposefully sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Nineteen studies [ 11 , 12 , 14 , 15 , 48 , 49 , 53 56 , 59 , 60 , 62 65 , 67 , 72 , 73 ] provided data about community engagement in HIV/AIDS-related research, while 14 studies [ 9 , 12 15 , 46 , 47 , 50 , 54 , 60 , 69 , 72 74 ] provided data on malaria-related research. The remaining studies provided data on Schistosomiasis [ 46 , 58 ], Ebola [ 45 , 68 ], tuberculosis [ 50 ], Lymphatic Filariasis [ 61 ], and Typhoid [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nineteen studies [ 11 , 12 , 14 , 15 , 48 , 49 , 53 56 , 59 , 60 , 62 65 , 67 , 72 , 73 ] provided data about community engagement in HIV/AIDS-related research, while 14 studies [ 9 , 12 15 , 46 , 47 , 50 , 54 , 60 , 69 , 72 74 ] provided data on malaria-related research. The remaining studies provided data on Schistosomiasis [ 46 , 58 ], Ebola [ 45 , 68 ], tuberculosis [ 50 ], Lymphatic Filariasis [ 61 ], and Typhoid [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the local context, the CAB plays multiple roles [ 55 ], which are crucial for the success of the research, from ensuring that the research fits and addresses the local needs and views to building trust and partnerships were also crucial in shaping the research strategy and effective implementation [ 74 ]. Thus, research institutes and academics must ensure functional and representative CAB that fully and responsibly operates in the entire research cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Intermediaries would largely mediate the discussion and decisions regarding benefit-sharing lather becoming ultimate decision-makers. Similar to other clinical trials, CAB in HIV vaccine trials, are made up of representatives from the community and usually act to advance the goals of the research community while protecting the interest of the researched community [ 29 ]. However, not all clinical trials will have a fully functioning CAB and this could create a loophole when deciding about benefits to be shared.…”
Section: Discussionmentioning
confidence: 99%
“…CAB review study details and offer feedback on proposed approaches with a goal of increasing study accessibility to the lay public ( Mitchell et al, 2020 ). Use of these strategies along with others can help to tailor ascertainment strategies, increase participation, and improve retention ( Wong et al, 2021 ; Pancras et al, 2022 ). A few of the reviewed trials reported use of a CAB in study development ( Ahluwalia et al, 2006 ; Cox et al, 2012 ; Lerman et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%